Recent Advances in Photocatalytic C–N Bond Coupling Reactions - Chan, Chun-Ming; Chow, Yip-Chi; Yu, Wing-Yiu (Synthesis, 2020)
Catalytic C–N bond formation is one of the major research topics in synthetic chemistry owing to the ubiquity of amino groups in natural products, synthetic intermediates and pharmaceutical agents. In parallel with well-established metal-catalyzed C–N bond coupling protocols, photocatalytic reactions have recently emerged as efficient and selective alternatives for the construction of C–N bonds. In this review, the progress made on photocatalytic C–N bond coupling reactions between 2012 and February 2020 is summarized.1 Introduction1.1 General Mechanisms for Photoredox Catalysis1.2 Pioneering Work2 C(sp2)–N Bond Formation2.1 Protocols Involving an External Oxidant2.2 Oxidant-Free Protocols3 C(sp3)–N Bond Formation3.1 Direct Radical–Radical Coupling3.2 Addition Reactions to Alkenes3.3 Reductive Amination of Carbonyl Compounds3.4 Decarboxylative Amination4 Cyclization Reactions4.1 C(sp2)–N Heterocycle Formation4.2 C(sp3)–N Heterocycle Formation5 Other Examples6 Conclusion and Outlook
Keywords: photochemistry; C–N cross-coupling; amination; radicals; visible light